Fluctuations of fluctuation-induced casimir-like forces. - Bartolo, D; Ajdari, A; Fournier, J; Golestanian, R (2002)
The force experienced by objects embedded in a correlated medium undergoing thermal fluctuations-the so-called fluctuation-induced force-is actually itself a fluctuating quantity. Using a scalar field model, we compute the corresponding probability distribution and show that it is a Gaussian centered on the well-known Casimir force, with a nonuniversal standard deviation that can be typically as large as the mean force itself. The relevance of these results to the experimental measurement of fluctuation-induced forces in soft condensed matter is discussed, as well as the influence of the finite temporal resolution of the measuring apparatus.